Protection against Schistosoma mansoni infection using a Fasciola hepatica-derived fatty acid binding protein from different delivery systems (2016)
BACKGROUND: Schistosomiasis is a water-borne disease afflicting over 261 million people in many areas of the developing countries with high morbidity and mortality. The control relies mainly on treatment with praziquantel. Fatty acid binding proteins (FABP) have demonstrated high levels of immune-protection against trematode infections. This study reports the immunoprotection induced by cross-reacting Fasciola hepatica FABP, native (nFh12) and recombinantly expressed using two different expression systems Escherichia coli (rFh15) and baculovirus (rFh15b) against Schistosoma mansoni infection. METHODS: BALB/c mice were vaccinated with native nFh12 or recombinant rFh15 and rFh15 FABP from F. hepatica formulated in adjuvant adaptation (ADAD) system with natural or chemical synthesised immunomodulators (PAL and AA0029) and then challenged with 150 cercariae of S. mansoni. Parasite burden, hepatic lesions and antibody response were studied in vaccination trials. Furthermore differences between rFh15 and rFh15b immunological responses (cytokine production, splenocyte population and antibody levels) were studied. RESULTS: Vaccination with nFh12 induced significant reductions in worm burden (83%), eggs in tissues (82-92%) and hepatic lesions (85%) compared to infected controls using PAL. Vaccination with rFh15 showed lower total worm burden (56-64%), eggs in the liver (21-61%), eggs in the gut (30-77%) and hepatic damage (67-69%) using PAL and AA0029 as immunomodulators. In contrast, mice vaccinated with rFh15b showed only reductions in eggs trapped in the liver and intestine (53 and 60%, respectively), and hepatic lesions (45%). We observed a significant rise in TNFα, IL-6, IL-2, IL-4 and high antibody response (IgG, IgG1, IgG2a, IgM and IgE) in mice immunised with either rFh15 or rFh15b. Moreover, mice immunised with rFh15b showed an increase in IFNγ and a decrease in B220 cells compared to untreated mice, and less production of IgG1 and IgM than in mice immunised by rFh15. CONCLUSIONS: Higher level of protection is obtained by using Fasciola hepatica-derived FABP protein against Schistosoma mansoni infection. Native FABP is more effective than both recombinant systems. It could be due to post-translational modifications or FABP isoform or changes in the recombinant proteins.